Simultaneous round-trip time-of-flight measurements with encoded acoustic signals - de Marziani, Carlos Manuel (2012)
In relative positioning systems, with the aim of estimating object positions, distances among them are computed in a cooperative way, usually by measuring times-of-flight from the signals that they emit. These emissions are often synchronized with additional signals or suitable hardware that acts as a temporal reference. In this paper, a ranging system is presented where only acoustic emissions are used to compute the distances between objects or nodes. Thus, an organization and operation algorithm is proposed, which provides a temporal reference to the acoustic emissions carried out by every node. In this way, distances are computed by determining the temporal relation between a request of emission from a coordinator node and the corresponding answers emitted by the other nodes. In order to simultaneously detect the acoustic emissions, the signals are encoded with complementary set of sequences allowing multisensory operation and accepting low signal-to-noise conditions. With this measurement scheme, additional signals and high accuracy clocks often used for synchronization can be eliminated, thus reducing hardware complexity, power consumptions, and possible interferences with other systems (i.e., if radio frequency signals are used). The simulation and experimental results show that sub-centimeter accuracy can be obtained with the proposed ranging scheme.